THE INFLUENCE OF SOCIAL INTERACTION AND ENVIRONMENT ON CHILDREN'S EMOTIONAL INTELLIGENCE: A DEVELOPMENTAL PSYCHOLOGY PERSPECTIVE - Ghadiza Chalil Tjan; Siti Munadiyah; Nurulsani S. Abd. Latief; Abdul Halil Hi. Ibrahim (Adisam Publisher, 2025)
Emotional intelligence is an important aspect of child development that influences their success in various aspects of life. This study examines the influence of social interaction and environment on the development of children's emotional intelligence from a developmental psychology perspective. Through a literature review and analysis of various empirical studies, it was found that positive social interaction and a supportive environment play a significant role in shaping and improving children's emotional intelligence. Factors such as parenting patterns, the quality of relationships with peers, and the school climate have a substantial impact on children's ability to recognise, understand, and manage emotions. The results of the study indicate that emotional intelligence can be trained and developed through appropriate interventions and the creation of a conducive environment. The implications of these findings emphasise the importance of collaboration between families, schools, and communities in supporting the development of children's emotional intelligence, as well as opening opportunities for further research on effective strategies to enhance children's emotional intelligence through social interaction and environmental modification.